MENINGKATKAN PARTISIPASI PEMILIH MELALUI KOMUNIKASI POLITIK - L.M. Azhar Sa'ban; Andy Arya Maulana Wijaya; La Doli (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Abstract: The purpose of this study (1) is to explain how the level of political participation of the community in the 2018 Regional Election in Baubau City (2) to identify any efforts made by the Baubau City Election Commission and political parties in increasing public political participation. Data were collected by analyzing documents, observing, interviewing, and analyzing with qualitative and quantitative descriptive techniques. The results of this study are: (1) The level of community participation in Baubau City is relatively high because if it is accumulated at 69.87%. (2) KPUD communication to increase public political participation is to use mass media to create society following the development of the Election process. (3) Communication of Political Parties to increase political participation of the community is this political campaign is a form of political communication carried out by a person or group of people or political organizations in a certain time to obtain political support from the people.Keywords: Political Communication, Political Participation, Regional Elections Baubau CityAbstrak: Tujuan penelitian ini adalah untuk menjelaskan bagaimana tingkat partisipasi politik masyarakat dalam Pemilihan Kepala Daerah tahun 2018 di Kota Baubau, serta mengidentifikasi upaya-upaya apa saja yang dilakukan KPUD Kota Baubau dan partai politik dalam meningkatkan partisipasi politik masyarakat. Data dikumpulkan dengan analisis dokumen, pengamatan, wawancara, dan dianalisis dengan tehnik deskriptif kualitatif dan Kuantitatif. Hasil dari penelitian ini adalah tingkat partispasi masyarakat di Kota Baubau tergolong tinggi dikarenakan jika diakumulasikan sebesar 69,87% %, komunikasi Komisi Pemilihan Umum Daerah (KPUD) Kota Baubau untuk meningkatkan partisipasi politik masyarakat adalah menggunakan media massa untuk menciptakan masyarakat mengikuti perkembangan proses Pemilu, dan Komunikasi Partai Politik untuk meningkatkan partisipasi politik masyarakat adalah kampanye politik ini merupakan bentuk komunikasi politik yang dilakukan oleh seseorang atau sekelompok orang atau organisasi politik dalam waktu tertentu untuk memperoleh dukungan politik dari rakyat.Kata Kunci: Komunikasi Politik, Partisipasi Politik, Pemilukada Baubau